2020
DOI: 10.1002/mnfr.201900991
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effects of Pterostilbene on the Exercise Intolerance and Circadian Misalignment of Mice Subjected to Sleep Restriction

Abstract: Scope The study investigates the effects of pterostilbene (PTE) on exercise endurance and circadian rhythm in sleep‐restricted (SR) mice. Methods and results The SR model is established by keeping mice awake during the first 8 h of light period for 5 d and PTE (100 mg kg−1 d−1) is given once a day. PTE improves endurance in SR mice by significantly prolonging the exhaustive swimming time and ameliorating exercise fatigue biochemical parameters, including creatine kinase and lactate dehydrogenase. It is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The experimental design is shown in Figure 1A and followed the National Research Council Guidelines. Animal experiment 1: the C57BL/6 mice ( n = 24) were randomly distributed into six groups ( n = 4/group), gavaged with pterostilbene (100 mg/kg/day) ( 30 ) at 9:00 a.m. and sacrificed at 0, 2, 6, 10, 12, and 24 h after intragastric administration, respectively. The contents of small intestine and colon were collected and stored at −80 ° C. Animal experiment 2: mice ( n = 48) were randomly divided into four groups ( n = 12/group): control group (CON), pterostilbene group (PTE), exercise group (EX), and exercise with pterostilbene group (EX + PTE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental design is shown in Figure 1A and followed the National Research Council Guidelines. Animal experiment 1: the C57BL/6 mice ( n = 24) were randomly distributed into six groups ( n = 4/group), gavaged with pterostilbene (100 mg/kg/day) ( 30 ) at 9:00 a.m. and sacrificed at 0, 2, 6, 10, 12, and 24 h after intragastric administration, respectively. The contents of small intestine and colon were collected and stored at −80 ° C. Animal experiment 2: mice ( n = 48) were randomly divided into four groups ( n = 12/group): control group (CON), pterostilbene group (PTE), exercise group (EX), and exercise with pterostilbene group (EX + PTE).…”
Section: Methodsmentioning
confidence: 99%
“…In the second week, referred to Bedford’s method ( 31 , 32 ), mice in exercise groups ran at the speed of 25 m/min until exhaustion one time a day for 7 days, and the exhaustion statue according to the literature reported ( 33 ). The PTE and EX + PTE groups were orally gavaged with pterostilbene (100 mg/kg/day) for 1 week, as previous study reported ( 30 ). The PTE was administered 12 h before exercise, and the mice of the EX and EX + PTE groups were sacrificed 1 h after the last exercise session.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial morphology and number in the gastrocnemius muscle were analyzed by TEM images. Briefly, gastrocnemius was treated and visualized on JEM-1400 microscope (Jeol, Japan) as we described before (Liu et al, 2020). Three animals per group were and ten images per mouse were used for the quantitative analysis of mitochondria.…”
Section: Transmission Electron Microscopy Observationmentioning
confidence: 99%
“…The number of mitochondria per section of intermyofibrillar mitochondria was quantified. The number of mitochondria was counted on micrographs as previously described (Liu et al, 2020).…”
Section: Transmission Electron Microscopy Observationmentioning
confidence: 99%
“…[ 32 ] Likewise, PSB also showed its regulative effect on exercise intolerant mice induced by restricted‐sleep via Adenosine monophosphate‐activated protein kinase (AMPK)/SIRT1/Peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α) pathway to clock genes expression of skeletal muscle. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%